Stomach / Stomaco (C16.9) - A case report of gastric metastases from malignant melanoma - Magenta, Gaetano; Alberti, Anna; Arigliano, Vincenzo; Maccaferri, Roberto; Bragagni, Giampaolo (European Journal of Oncology and Environmental Health, 2014)
Background: The gastrointestinal tract is an apparently unusual site of metastases from malignant melanoma. Clinical picture: We present a case of an elderly patient hospitalized at our Unit for severe anemia associated with dyspeptic disorders, who a year earlier had undergone the removal of a melanoma of the skin of the left calf. Results: The EGDS found two large ulcerated lesions of gastric mucosa, which proved at histological examination to be metastases from melanoma. Conclusion: The presence of anemia and/or digestive symptoms in a patient with previous history of melanoma could indicate a gastrointestinal tumor localization.